Effect of prescribed burning on the nutritional value of aerial Schoenoplectus tatora stems, Lake Titicaca, Peru. (Bioagro, 2022)
Prescribed burning of cattails is a frequent practice in coastal areas of Lake Titicaca in order to eliminate senescent biomass, obtain tender shoots and better nutritional quality as forage. Therefore, objective of the study was to determine effects of these burns on the nutritional value of aerial cattail stems, through proximal analyzes after burning for two consecutive years, comparing with cattails without burning for five years, in three phenological periods (sprouting, growth, and maturation), submitting the data under Anova with factorial arrangement 2*3 (two treatments, and three seasons) and Tukey's test. According to results, dry matter in cattails with burning increased significantly (P
Keywords: Forage; fire; nutrients; Titicaca; cattails